In situ Rheo-GISANS of triblock copolymers: gelation and shear effects on quasi-crystalline structures at interfaces. Issue 126 (9th December 2015) - Newby, Gemma E.; Watkins, Erik B.; Merino, Daniel Hermida; Staniec, Paul A.; Bikondoa, Oier
Abstract : The behaviour of polymeric systems at surfaces and under flow is very important in many applications, from drug delivery to lubrication. Here, we have studied the thermotropic phases formed by a model tri-block copolymer using in situ Rheo-GISANS. Abstract : The behaviour of polymeric systems at surfaces and under flow is extremely important in many applications, ranging from drug delivery to lubrication. We have studied a model triblock copolymer in deuterated water combining in situ rheology and grazing incidence small angle neutron scattering. Several thermotropic phases appear as a function of the temperature, including a bicontinuous phase not present in the bulk. Moreover, gelation can occur following a different route depending on the concentration. We show that shearing can be used to monitor the structural integrity of the micellar systems and in some cases as a tool for modifying the thermotropic phases: an fcc (face centred cubic) phase is sheared into a hcp (hexagonally close packed) phase, and is then recovered by cycling the temperature.